Opportunistic detection of colorectal cancer by the family doctor (Portuguese Journal of Family Medicine and General Practice, 2007)
Introduction: In Portugal, colorectal cancer (CRC) is nowadays the type of cancer with the highest specific mortality rate, which is progressively increasing in the last 20 years. Fecal occult blood test (FOBT) is the only screening method that has been shown to reduce CRC specific mortality (15 to 33%) by means of population-based randomised trials, methodology supported by the National Oncology Plan 2001-05. The UK Department of Health carried out a Pilot Study to test the feasibility of a national screening program for CRC using FOBT, whose short term outcomes achieved at the key parameters in the prevalence (first) round were comparable to those of the Nottingham randomised controlled trial. Objectives: 1- To describe the key parameters of the CRC opportunistic detection based on FOBT in a patient list (uptake and positivity rates of FOBT, uptake rate of colonoscopy, positive predictive value of a positive test for neoplasia and neoplasia detection rate); 2- To compare the results achieved in the study with those of the Nottingham standard trial. Methodology: Cross-sectional descriptive study with an internal analytical component. Non-randomized convenience sample: 50 to 74 year old patients who have attended a consultation from 3 March 2004 till 3 March 2006 without exclusion criteria (n=275). Studied variables: (1) Uptake rate of FOBT; (2) Positivity rate of FOBT; (3) Uptake rate of colonoscopy; (4) Positive predictive value of a positive test for adenoma; (5) Adenoma detection rate. Results: Among the target-population, 275 patients attended a consultation from 3 March 2004 till 3 March 2006 and were invited to perform a FOBT; from those, 5 have declined. From the 31 patients who have had a positive test, 2 refused to perform a colonoscopy. The following investigation revealed 3 adenomatous polyps and no cancer. (1) Among the target-population without exclusion criteria that attended a consultation (275), 270 (98%) completed the test, a higher uptake than Nottingham (59,6%) (p
Keywords: Colorectal Cancer; Adenoma; Opportunistic Detection